Long-term safety and efficacy of ozanimod in relapsing multiple sclerosis: Up to 5 years of follow-up in the DAYBREAK open-label extension trial - Cree, Bruce Ac; Selmaj, Krzysztof W; Steinman, Lawrence; Comi, Giancarlo; Bar-Or, Amit; Arnold, Douglas L; Hartung, Hans-Peter; Montalbán, Xavier; Havrdová, Eva K; Sheffield, James K; Minton, Neil; Cheng, Chun-Yen; et al. (Multiple sclerosis (Houndmills, Basingstoke, England), 2022)
BACKGROUND: Ozanimod, an oral sphingosine 1-phosphate receptor 1 and 5 modulator, is approved in multiple countries for treatment of relapsing forms of MS. OBJECTIVE: To characterize long-term safety and efficacy of ozanimod. METHODS: Patients with relapsing MS who completed a phase 1‒3 ozanimod trial were eligible for an open-label extension study (DAYBREAK) of ozanimod 0.92 mg/d. DAYBREAK began 16 October 2015; cutoff for this interim analysis was 2 February 2021. RESULTS: This analysis included 2494 participants with mean 46.8 (SD 11.9; range 0.033‒62.7) months of ozanimod exposure in DAYBREAK. During DAYBREAK, 2143 patients (85.9%) had treatment-emergent adverse events (TEAEs; similar in nature to those in the parent trials), 298 (11.9%) had a serious TEAE, and 75 (3.0%) discontinued treatment due to TEAEs. Serious infections (2.8%), herpes zoster infections (1.7%), confirmed macular edema cases (0.2%), and cardiac TEAEs (2.8%) were infrequent. Adjusted annualized relapse rate was 0.103 (95% confidence interval, 0.086‒0.123). Over 48 months, 71% of patients remained relapse free. Adjusted mean numbers of new/enlarging T2 lesions/scan and gadolinium-enhancing lesions were low and similar across parent trial treatment subgroups. CONCLUSIONS: This long-term extension of ozanimod trials confirmed a favorable safety/tolerability profile and sustained benefit on clinical and magnetic resonance imaging measures of disease activity.
Keywords: Multiple Sclerosis, Relapsing-Remitting; indany; Sphingosine-1-Phosphate Receptors; ozanimod; sphingosine 1-phosphate receptor modulators; recidiva; Follow-Up Studies; clinical efficacy; následné studie; receptory sfingosin-1-fosfátu; oxadiazoly; Humans; Recurrence; Indans; Multiple sclerosis; relabující-remitující roztroušená skleróza; Oxadiazoles; adverse events; extension study; lidé